Detection and Prevention of ARP Cache Poisoning in Advanced Persistent Threats Using Multiphase Validation and Firewall - Al-Mwald M.N.; Jamil N.; Ibrahim Z.A.; Cob Z.C.; Abdul Rahim F. (Springer Science and Business Media Deutschland GmbH, 2023)
Security of data; Security systems; Address Resolution Protocol; Address resolution protocol cache poisoning; Address resolution protocol spoofing attack; Cache poisoning; Internet control message protocol protocol; Internet control message protocols; MITM; Spoofing attacks; Internet protocols